2010
DOI: 10.1073/pnas.0911249107
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts between adaptive coding and noncoding changes during human evolution

Abstract: Changes in non-protein-coding regulatory DNA sequences have been proposed to play distinctive roles in adaptive evolution. We analyzed correlations between gene functions and evidence for positive selection in a common statistical framework across several large surveys of coding and noncoding sequences throughout the human genome. Strong correlations with both classifications in gene ontologies and measurements of gene expression indicate that neural development and function have adapted mainly through noncodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 30 publications
9
102
0
4
Order By: Relevance
“…It is thought that one of the major evolutionary drivers of the complexity of the human brain is the non-coding transcriptome (Haygood et al 2010). Indeed, the human brain and, in particular, the frontal cortex, appears to be a rich source of lincRNAs (Mills et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that one of the major evolutionary drivers of the complexity of the human brain is the non-coding transcriptome (Haygood et al 2010). Indeed, the human brain and, in particular, the frontal cortex, appears to be a rich source of lincRNAs (Mills et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent analyses of the human genome suggest a distinctive role for adaptative changes both in coding and non-coding sequences. Changes in non-coding sequences appear primarily related to changes in neural development (Haygood et al, 2010). The last decade has witnessed an explosion of studies showing that the complex regulation of gene expression is mainly modulated by the manifold interactions between transcription factors (TFs) with their corresponding transcription factors binding sites (TFBSs) on DNA (Wei & Yu, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most fundamental and unanswered questions is whether adaptative evolution proceeds through changes in protein-coding DNA sequences or through non-coding regulatory sequences. It has been argued that morphological change occurs mainly via non-coding changes (Haygood et al, 2010). Diptera studies showed that cis-regulatory sequences that control transcription are a common source of divergent protein expression patterns and thus of phenotypic change (Wittkopp, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Graças à grande quantidade de scans genômicos em busca de assinaturas de seleção positiva, sabe-se hoje que muitos dos genes com tais assinaturas estão relacionados com certas categorias: "imunidade e defesa", "percepção sensorial" e "imunidade mediada por células T", "gametogênese", "espermatogênese e mobilidade" (Harris e Meyer, 2006;Nielsen et al, 2005). Para as regiões não-codificadoras, destacam-se processos biológicos como "neurogênese", "outras atividades neuronais" e "desenvolvimento muscular" (Haygood et al, 2010).…”
Section: Evolução Adaptativa No Genoma Humanounclassified